Sistem Pendukung Keputusan Pemilihan Asisten Laboratorium Menggunakan Metode Simple Additive Weighting (SAW) - Rosmiati, Rosmiati (STMIK Palangkaraya, 2016)
Acceptance laboratory assistant in STMIK of Palangka Raya is one example of a case in making decision.Lecturers who became a selector of a practicum lecture will do selection acceptance assistant to the student who has registered as a candidate for assistant so that the process undertaken inaccurate in the selection process. the role of information technology is expected to be used to assist the lecturer in the process of acceptance of a laboratory assistant, so as to speed up the process and can produce the best decisions about anyone assistants who is received so that made the supporting system of decision selection laboratory assistant in STMIK of Palangka Raya which use method of Simple Additive Weighting (SAW). To make this system uses a method of SAW and the programming language used is Microsoft Visual Basic 6.0, then the system is developed using development method of software waterfall with design tools such as DFD (Data Flow Diagram) , ERD (Entity Relationship Diagram) and Database. With there is the Decision Support System that can be easier for STMIK of Palangka Raya in aiding the selection of a laboratory assistant so that can improve the quality of laboratory assistant.